Perceptions of students’ online learning experience during the Covid-19 pandemic in the state of Nagaland: Are teachers dispensable or indispensable actors in an era of digital education? - Awomi, Niboli T (Voices of Teachers and Teacher Educators, 2022)
This study examines students’ perceptions of the online mode of learning during the Covid-19 pandemic in the state of Nagaland. It also seeks to understand students’ perceptions of the role of teachers in their learning process. The sample comprised 80 students, who were pursuing bachelor’s programs in the colleges of Nagaland, India. Tools for gathering data include interviews and questionnaires. Data gathered emphasized three aspects of online learning—students’ motivation for online learning; students’ digital competency; and students’ perceptions of the role of teachers in their learning process. One significant finding on the first aspect indicates students’ lack of interest and motivation owing to issues such as internet connectivity and the ratio of students to the teacher in the classroom. In the second aspect, it was found that there is a gap between the level of students’ expected digital competency and their actual digital competency; and on the roles of teachers, students’ perceptions of teachers as mentors necessitate their indispensability in the learning process. The study has implications for a pedagogical discourse for promoting scientific inquiry in pre-service teacher education program.